2017
DOI: 10.1002/cbin.10777
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia upregulates integrin gene expression in microvascular endothelial cells and promotes their migration and capillary‐like tube formation

Abstract: Tissue hypoxia affects gene expression through the hypoxia-inducible transcription factors, HIF-1 and HIF-2, in both physiological and pathological angiogenesis. Angiogenesis is a complex response of endothelial cells integrating cell proliferation, migration, tube formation, and their interaction with the extracellular matrix through integrin receptors. In this report, we studied the effect of hypoxia on the angiogenic functions of human microvascular endothelial cells (HMEC-1) as well as on expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Additionally, previous studies have shown that vascular endothelial cells are produced under hypoxic conditions, which enhance microvessel proliferation. Consistent with these findings, we observed that, under hypoxia, the MVD increased because the vascular endothelial cells are produced [46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, previous studies have shown that vascular endothelial cells are produced under hypoxic conditions, which enhance microvessel proliferation. Consistent with these findings, we observed that, under hypoxia, the MVD increased because the vascular endothelial cells are produced [46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 88%
“…Hypoxia has been shown to induce the expression of MMP2 and MMP9, which are important molecules for tumor cell invasion and metastasis [23][24][25]. In addition, hypoxia-induced integrin β3 expression can affect endothelial cell tube formation [26].…”
Section: Hypoxia and Its Evolutionary Role During Angiogenesismentioning
confidence: 99%
“…To induce HIF1α production, adipocytes were cultured under hypoxia (2% O 2 ) plus the HIF1α stabilizer, (DMOG, 500 µM) as previously described [19] [20]. We tested three different concentrations of CAY10585 (10, 20, and 30µM), which decreased the nuclear fraction of HIF1α protein, by 55%, 74%, and 90%, respectively ( Figure 1D).…”
Section: Description Of Experimental Modelsmentioning
confidence: 99%